The Influence of Social Media Marketing Activities on the Satisfaction of Members of the Entrepreneurs Online Community in Yogyakarta - Natasya Budi Ayu Satriadita (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
The Internet is increasingly utilized not only as an information source but also as a marketing platform, particularly through social media. In line with this trend, many firms and digital communities leverage social media to enhance engagement and promotional activities. This study investigates the influence of Social Media Marketing Activities (SMMA) on member satisfaction within an online entrepreneurial community in Yogyakarta, Indonesia. Primary data were collected via an online questionnaire distributed through Google Forms to 200 respondents, selected using purposive non-probability sampling. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) with AMOS version 22. The results indicate that SMMA positively affects social identification, perceived value, and satisfaction. Additionally, social identification significantly enhances perceived value and satisfaction, while perceived value also positively contributes to satisfaction.